2015
DOI: 10.1007/s00018-015-1856-8
|View full text |Cite
|
Sign up to set email alerts
|

Instability restricts signaling of multiple fibroblast growth factors

Abstract: Fibroblast growth factors (FGFs) deliver extracellular signals that govern many developmental and regenerative processes, but the mechanisms regulating FGF signaling remain incompletely understood. Here, we explored the relationship between intrinsic stability of FGF proteins and their biological activity for all 18 members of the FGF family. We report that FGF1, FGF3, FGF4, FGF6, FGF8, FGF9, FGF10, FGF16, FGF17, FGF18, FGF20, and FGF22 exist as unstable proteins, which are rapidly degraded in cell cultivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…It is expected that binding of more stable FGF2 to FGFRs stabilized the FGFR dimers, increasing their signaling efficiency. This is evidenced in our previous article where both magnitude and duration of FGFR activity correlated precisely with the thermodynamical stability of multiple wild-type FGFs (Buchtova et al, 2015). Moreover, as demonstrated by ligand-washing experiments (Figure 8), the stable FGF2 associated for a longer time with FGFRs at the cell surface, suggesting a greater stability of the FGFR dimers.…”
Section: In Vitro Biological Characterization Of Cumulative Fgf2 Musupporting
confidence: 75%
See 1 more Smart Citation
“…It is expected that binding of more stable FGF2 to FGFRs stabilized the FGFR dimers, increasing their signaling efficiency. This is evidenced in our previous article where both magnitude and duration of FGFR activity correlated precisely with the thermodynamical stability of multiple wild-type FGFs (Buchtova et al, 2015). Moreover, as demonstrated by ligand-washing experiments (Figure 8), the stable FGF2 associated for a longer time with FGFRs at the cell surface, suggesting a greater stability of the FGFR dimers.…”
Section: In Vitro Biological Characterization Of Cumulative Fgf2 Musupporting
confidence: 75%
“…The long‐term maintenance of growth factors in the tissue or media is desirable for protein therapies and stem cell culturing, but is hindered by the low thermal stability of the molecules and their limited half‐life (Beenken & Mohammadi, ; Buchtova et al, ; Chen, Gulbranson, Yu, Hou, & Thomson, ). Stability of FGFs was shown to be enhanced by co‐administration with heparin (Furue et al, ), conjugation to heparin‐mimicking polymers (Nguyen et al, ; Paluck, Nguyen, Lee, & Maynard, ), encapsulation in microspheres (Lotz et al, ), or fusion with proteoglycan (Yoneda, Asada, Oda, Suzuki, & Imamura, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heparin by itself had no effect. Among the many FGF isoforms, FGF2 was used because it activates FGFR3 as well as FGFR2, and older data indicate that both receptors are expressed in RCS cells [32, 38]. However, more recent data by Chapman et al demonstrated that the mRNA for FGFR3 is 8-fold higher than FGFR1, which is 100-fold higher than FGFR2 and 50-fold higher than FGFR4 [31].…”
Section: Resultsmentioning
confidence: 99%
“…The long-term maintenance of growth factors in the tissue or media is desirable for protein therapies and stem cell culturing, but is hindered by low thermal stability of the molecules and their limited half-life 1,9,10 . Stability of FGFs was shown to be enhanced by coadministration with heparin 11 , conjugation to heparin-mimicking polymers 12 , encapsulation in microspheres 13 , or fusion with proteoglycan 14 .…”
Section: Introductionmentioning
confidence: 99%